The nuclear export of TR3 mediated gambogic acid-induced apoptosis in cervical cancer cells through mitochondrial dysfunction. Issue 21 (16th April 2019) - Zhang, Chunhong; Liu, Jia; Tao, Fengxing; Lu, Yiyi; He, Qin; Zhao, Liang; Ou, Rongying; Xu, Yunsheng; Li, Wenfeng
Abstract : The crosstalk of TR3 and p53 mediates GA-induced apoptosis of cervical cancer cells. Abstract : At present, chemotherapy is still the main treatment for cervical cancer. However, the drug resistance of chemotherapy drugs seriously restricts its use, so it is urgent to develop new drugs for cervical cancer. Some studies have shown that gambogic acid has a strong anti-tumor effect, while the anti-tumor effect and molecular mechanism of gambogic acid on cervical cancer need to be studied. Our study confirms that the cytotoxic effect of gambogic acid on cervical cancer cells depends on the expression of TR3 protein. Moreover, gambogic acid-induced apoptosis requires TR3 expression. In the mechanism, gambogic acid promoted nuclear export of TR3, resulting in up-regulation of p53, which leads to the decrease of mitochondrial membrane potential, eventually inducing apoptosis. These results suggest that the nuclear export of TR3 mediated gambogic acid-induced apoptosis through a p53-dependent apoptosis pathway.